2015
DOI: 10.1016/j.phytochem.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and SAR studies of bicyclic iminosugars from Castanospermum australe as glycosidase inhibitors

Abstract: We report the isolation and structural determination of fourteen iminosugars, containing five pyrrolizidines and five indolizidines, from Castanospermum australe. The structure of a new alkaloid was elucidated by spectroscopic methods as 6,8-diepi-castanospermine (13). Our side-by-side comparison between bicyclic and corresponding monocyclic iminosugars revealed that inhibition potency and spectrum against each enzyme are clearly changed by their core structures. Castanospermine (10) and 1-deoxynojirimycin (DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In various studies, the ability of CAS to prevent the rejection of organ transplants has been evaluated (33), and it has been shown to display antiviral activity against retroviruses including HIV (34,35). Combination therapy of 6-O-butanoyl castanospermine (Celgosivir) with peginterferon and/or ribavirin has been undergoing investigation in phase II clinical trials for the treatment of patients with chronic HCV (36). CAS significantly inhibits tumor growth in nude mice, reduces the adhesion of tumor cells to the vascular endothelium, and decreases antimetastatic activity by inhibiting platelet aggregation of metastatic cells (32).…”
Section: Effect Of Brefeldin a And Castanospermine On Resistant Cell mentioning
confidence: 99%
“…In various studies, the ability of CAS to prevent the rejection of organ transplants has been evaluated (33), and it has been shown to display antiviral activity against retroviruses including HIV (34,35). Combination therapy of 6-O-butanoyl castanospermine (Celgosivir) with peginterferon and/or ribavirin has been undergoing investigation in phase II clinical trials for the treatment of patients with chronic HCV (36). CAS significantly inhibits tumor growth in nude mice, reduces the adhesion of tumor cells to the vascular endothelium, and decreases antimetastatic activity by inhibiting platelet aggregation of metastatic cells (32).…”
Section: Effect Of Brefeldin a And Castanospermine On Resistant Cell mentioning
confidence: 99%
“…Castanospermine is another alkaloid extracted from Castanospermum australe A. Cunn ex Hook. [98] and is reported to convert protein N-linked high mannose carbohydrates to complex oligosaccharides. Castanospermine serves as an inhibitor of the glycosidases and leads to the suppression of tumor cell proliferation in nude mice [160].…”
Section: Alkaloidsmentioning
confidence: 99%
“…4 Its relative configuration was assigned by NMR analysis and its absolute configuration was established later following the synthesis of an authentic sample {[α]D 20 +21.6 (c 0.36 in H2O)}, 5 derived from D-glucose 1, which was reported by Fleet and co-workers. 5 D-Fagomine 3 and glycosides of D-fagomine have been isolated from various natural sources for example the seeds of Castanospermum australe (Leguminosae), 6,7 the seeds of the African legume Angylocalyx pynaertii, 8 the seeds of Xanthocericis zambesiaca, 9 the leaves of Morus bombycids, 2a the roots of Lycium Chinese, 10 the root bark of Morus alba L., 2d the pods of Angylocalyx pynaertii, 11 and from traditional Chinese medicines such as Faeces bombycis 12 and mulberry leaf (Morus alba L.). 13 Also, D-5-epi-fagomine 6 (also known as D-3,4-di-epi-fagomine) 15 Since its first isolation in 1974, many biological studies of D-fagomine 3 and its stereoisomers have been reported.…”
Section: Introductionmentioning
confidence: 99%